Arterial Access Port: A Shunt‐Less Vascular Access Using a Blind‐Ending Artificial Graft Anastomosed to the Brachial Artery. Issue 2 (13th March 2017) - Matsuda, Hiroaki; Oka, Yoshinari; Yoshida, Ryuichi; Katsura, Yuki; Takeuchi, Hidemi; Oyama, Takanori; Takatsu, Shigeko; Miyazaki, Masashi
Abstract: We retrospectively investigated the usability of arterial access ports (AAPs), which are blind‐ending short prosthetic grafts anastomosed to the brachial artery (BA) and implanted subcutaneously, via which cannulation and blood‐drawing from the BA was performed. Nineteen AAPs in 16 patients were evaluated. The AAP cumulative functional usage rate tended to drop within a year after its implantation because of infection and inappropriate positioning; however, its usability was extended for a maximum of 97 months after re‐implantation. The operative modification of minimal superficial repositioning of the BA anastomosed with the graft significantly improved its usage rate by easing the cannulation via the graft and eliminated usage withdrawal caused by infection and dislocation. Occlusion, thrombus, and ligation of the BA never occurred even after surgical repairs for infectious AAP. The use of an AAP as a shunt‐less vascular access could be an alternative to BA superficialization with avoidance of direct BA puncture.